2013
DOI: 10.1108/jepp-11-2011-0027
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific effects of the Sarbanes-Oxley Act

Abstract: Purpose -The purpose of this paper is to empirically demonstrate that drivers of venture capital (VC) investments are different across three broadly defined sectors: high-technology manufacturing, medium-technology manufacturing and services, and low-technology services. Moreover, such differences also exist across industries within each of these sectors. Design/methodology/approach -The basic hypothesis is that "not only different stages of VC investments have different drivers, but VC investments in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A recent study by Félix et al (2013) found that, there is a statistically significant positive relationship between IPO and venture capital supply and concluded that among all the authors indicated above the only previous study that obtained a statistically positive relationship between IPO and venture capital supply at the later stage was Jeng and Wells (2000). Ecer and Khalid (2013) discovered that there is a significant negative relationship between IPO and venture capital supply for High technology firms and a significant positive relationship between IPO and venture capital supply for Low technology firms. Henderson and Newell (2011) in a study conducted in USA found that a reduction in IPO has a negative effect on venture capital supply.…”
Section: Literature Reviewmentioning
confidence: 98%
“…A recent study by Félix et al (2013) found that, there is a statistically significant positive relationship between IPO and venture capital supply and concluded that among all the authors indicated above the only previous study that obtained a statistically positive relationship between IPO and venture capital supply at the later stage was Jeng and Wells (2000). Ecer and Khalid (2013) discovered that there is a significant negative relationship between IPO and venture capital supply for High technology firms and a significant positive relationship between IPO and venture capital supply for Low technology firms. Henderson and Newell (2011) in a study conducted in USA found that a reduction in IPO has a negative effect on venture capital supply.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Further, they help in marketing, supplier selection, and connections, which leads to sustainability. Consistent with Ecer & Khalid (2013), they found that VCs assisted startups' expansion with hands-on involvement in marketing, management, and planning activities.…”
Section: Resultsmentioning
confidence: 56%
“…In this context, private funders might use these signals for investment decisions. Ecer & Khalid (2013) presumed that VCs with extensive industry experience tend to boost their investments when the public markets' signs are favorable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the determinants of VC investments, there is evidence that VC investors perform their own detailed due diligence (Smith and Cordina, 2014) and that their investment is facilitated by the IPO exit route, except for later development stages firms (Ecer and Khalid, 2013).…”
Section: International Studiesmentioning
confidence: 99%